2020
DOI: 10.1002/adfm.201909222
|View full text |Cite
|
Sign up to set email alerts
|

Auger Effect Assisted Perovskite Electroluminescence Modulated by Interfacial Minority Carriers

Abstract: Perovskite‐based light‐emitting diodes (PeLEDs) have exhibited promising potential; however, their operational lifetimes are far from expectation. The large bias of the device during operation has been demonstrated as one of main reasons for accelerated device failure. To mitigate such a predicament, interfacial Auger effect (IAE) assisted sub‐bandgap voltage electroluminescence (EL) is a potential pathway to decrease the electric field intensity in each functional layer. However, the properties of a desirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Further improvement of the EQE and stability should involve the better surficial passivation by organic ligands, to suppress the traps‐related leakage and nonradiative recombination, and the interface engineering to boost the light outcoupling and heat dissipation. [ 3–7,38–42 ]…”
Section: Resultsmentioning
confidence: 99%
“…Further improvement of the EQE and stability should involve the better surficial passivation by organic ligands, to suppress the traps‐related leakage and nonradiative recombination, and the interface engineering to boost the light outcoupling and heat dissipation. [ 3–7,38–42 ]…”
Section: Resultsmentioning
confidence: 99%
“…Interfacial Auger effect (IAE)‐assisted sub‐bandgap voltage EL was reported as a potential pathway to decrease the operating voltage in PeLEDs. [ 161 ] Low operational voltage and negligible efficiency roll‐off by taking advantage of the IAE‐assisted EL may be considered as a feasible approach to improve the lifetime as well as stability of device. Taking into account their significant effects on the interface and defect passivation of perovskites, the development of ideal CTLs should be conducted concurrently along with various strategies to improve the properties of perovskite EMLs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the use of small‐molecular CTLs has mainly been limited to vapor‐deposited ETLs in the p−i−n devices and HTLs in n−i−p devices, [ 56,57 ] due to the lack of orthogonal solvents for layer‐by‐layer processing of the CTLs and MHPs. In addition to TPBi, [ 16,18,58 ] several organic semiconductors, including 4,6‐bis(3,5‐di(pyridin‐3‐yl)phenyl)‐2‐methylpyrimidine (B3PyMPM), [ 13 ] 1,3,5‐Tri(m‐pyridin‐3‐ylphenyl)benzene (TmPyPb), [ 59 ] and 2,4,6‐Tris[3‐(diphenylphosphinyl)phenyl]‐1,3,5‐triazine (PO‐T2T), [ 60 ] have been found to be suitable for high‐performance PeLEDs. The higher electron mobilities and triplet energy, as well as deeper highest occupied molecular orbital levels, enable efficient electron transport, hole blocking, and exciton confinement.…”
Section: The Road To Commercializationmentioning
confidence: 99%
“…Recently, Liao and coworkers showed that the use of PO‐T2T could allow sub‐bandgap turn‐on voltages facilitated by Auger‐assisted charge injection. [ 60 ] While highly efficient PeLEDs could be obtained with vapor‐deposited ETLs, the rationale behind the choice of ETLs is not well understood and further studies on the interactions between ETLs and MHP layers are needed. Unlike small molecules that could only be processed using vapor deposition, many polymeric CTLs could be solution processed together with MHP layers using orthogonal solvents, particular polymeric HTLs, including poly(9‐vinylcarbazole) (PVK), [ 61 ] poly(9,9‐dioctylfluorene‐alt‐ N ‐(4‐sec‐butylphenyl)‐diphenylamine) (TFB), [ 21 ] and poly( N,N' ‐bis‐4‐butylphenyl‐ N,N' ‐bisphenyl)benzidine (poly TPD).…”
Section: The Road To Commercializationmentioning
confidence: 99%